Modeling of tidal currents effect on PersianGulf density using MIKE model - Omid Mahpeykar; Mohammadreza Khalilabadi (تحقیقات کاربردی علوم جغرافیایی)
General circulation of Persian Gulf has a cyclonic pattern that affected by tide, wind stress and thermohaline force. Although tidal force is very effective in values of current speed, but thermohaline force is dominant in long time because tidal forcing has a short period and returning nature. Tide and density parameters are important in navigating and shipping, especially when ships approaching the shore and shallow water to determine the drainage of them. In this study using the Mike model based on the three-dimensional solution of the Navier Stokes equations, assumption of incompressibility, Boussinesq aproximation, and hydrostatic pressure, Persian Gulf circulation modelled. After model stability, the effects of tidal force on horizontal and vertical distribution of density were investigated. Results show that forcing of tide caused current direction be regular and without tidal force, wind stress dominates on isopycnal and turbulent pattern forms in sea surface layer especially in cool season. Also, with the elimination of the tide effect, the velocity of current is reduced to 75% and the water density is increased to 1-2 kg/m3. Density profile show that the Persian Gulf is a baroclinic environment and it is stronger in cool season relative to warm season. The impact of forces is not the same in different regions of the Persian Gulf, so that the effects on the change in density in the Strait of Hormuz are more perceptible and moving inward to the Gulf, the intensity of its effect is reduced.